Digital economy, spatial spillover and industrial green innovation efficiency: Empirical evidence from China. Issue 1 (January 2023) - Li, Guangqin; Li, Xiaoge; Huo, Lingzhi
Abstract: The digital economy is pushing more efficient and greener production and innovation processes, as well as quickening the mobility of production factors, which would have a critical impact on improving industrial green innovation efficiency. Based on the panel data of 30 Chinese provinces from 2005 to 2019, this study established a comprehensive index system to assess the level of provincial digital economy development, and adopted the SBM-DEA model including non-expected output to evaluate industrial green innovation efficiency, then adopted the Global Moran's I and Local Moran's I to test whether there is spatial autocorrelation, followed by the spatial Durbin model (SDM) and the mediating effect test model to investigate the direct impact, spatial spillover effect and indirect transmission mechanism of the digital economy on industrial green innovation efficiency. The results show that: both the development level of the digital economy and industrial green innovation efficiency show positive spatial autocorrelation; The digital economy not only has a significant direct role in promoting industrial green innovation efficiency but also has a spatial spillover effect; The digital economy can improve industrial green innovation efficiency by promoting manufacturing structure upgrading and stimulating enterprises' green technology innovation. The findings of this paper are helpful for policymakers to clarify the relationship between the digital economy and industrial green innovation efficiency and provide favorable policy directions for developing the digital economy to promote industrial green innovation efficiency.